The Contemporary Christian Current in Lebanon - Dr. taghreed hnoon ALi; dr. sabrein satir gabir (The college of law and political science journal, 2023)
The Christian religious current is among the most prominent intellectual currents that contributed to the intellectual, political and social renaissance witnessed by the Lebanese society through its scholars and thinkers who called for the necessity of interaction with Western human thought based on philosophical thinking, and on the principles of Western revolutions in order to reform and correct social, economic and cultural conditions This trend also contributed to the emergence and formation of the independent Lebanese state, and this was exemplified by the efforts made by Howayek, who was called the man of independence.And the inspirer of Greater Lebanon, and the thinkers of this current had a great role in informing the Lebanese citizen of his rights and freedoms and demanding them, in addition to their demand for reforming the social, economic and political conditions. Islamic-Christian. Our research focused on the enlightenment reform trend of the contemporary Christian trend in Lebanon